2007
DOI: 10.1186/1471-2156-8-55
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTL with effects on intramuscular fat content and fatty acid composition in a Duroc × Large White cross

Abstract: Email: Marie-Pierre Sanchez -marie-pierre.sanchez@jouy.inra.fr; Nathalie Iannuccelli -nathalie.iannuccelli@toulouse.inra.fr; Benjamin Basso -benjamin.basso@toulouse.inra.fr; Jean-Pierre Bidanel -jean-pierre.bidanel@jouy.inra.fr; Yvon Billon -yvon.billon@magneraud.inra.fr; Gilles Gandemer -gilles.gandemer@lusignan.inra.fr; Hélène Gilbert -helene.gilbert@jouy.inra.fr; Catherine Larzul* -catherine.larzul@jouy.inra.fr; Christian Legault -catherine.larzul@jouy.inra.fr; Juliette Riquet -juliette.riquet@toulouse.inra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 33 publications
7
45
1
Order By: Relevance
“…However, the same authors have also located several small QTL with reduced individual effects afterwards. In Duroc pig population, Sanchez et al (2007) further indicated that the putative major gene corresponded in fact to two QTL.…”
Section: Genetic and Genomic Markers Of Imf Contentmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the same authors have also located several small QTL with reduced individual effects afterwards. In Duroc pig population, Sanchez et al (2007) further indicated that the putative major gene corresponded in fact to two QTL.…”
Section: Genetic and Genomic Markers Of Imf Contentmentioning
confidence: 93%
“…Considerable efforts have been made during the past decades to identify quantitative trait loci (QTL) for IMF (de Koning et al, 1999 andSanchez et al, 2007; Finally, the existence of a major gene with a great effect on IMF content has been postulated by segregation analysis (Janss et al, 1997). The gene, named MI, has a recessive allele (imf) that increases IMF content and originates from the Chinese Meishan pig breed.…”
Section: Genetic and Genomic Markers Of Imf Contentmentioning
confidence: 99%
“…The average distance between adjacent markers was 24.6 cM on the sexaveraged map (see Sanchez et al (2007) for the genetic map). One to six F1 boars were heterozygous (4.4 in average) for the 91 microsatellite markers.…”
Section: Molecular Analysesmentioning
confidence: 99%
“…Stress hormone levels, which have been found to be related to meat quality in the F2 population (Foury et al, 2005), and major production traits were also measured. The F2 Duroc 3 Large White population has already allowed detecting QTL for intramuscular fat content and fatty acid composition in the longissimus dorsi muscle (Sanchez et al, 2007). In this study, we investigated the QTL for other meat quality criteria, stress hormone levels and the main growth and carcass traits.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative trait locus analysis has indicated that the fatty acid composition of livestock species is regulated by many potential candidate genes with small effects (Taylor et al, 1998;Sanchez et al, 2007;Abe et al, 2008). Additionally, differential expression of adipogenic factors is known to play a key role in regulating multiple responsive pathways involved in fat development and lipid metabolism in cattle adipocytes .…”
Section: Other Genes Associated With Fatty Acid Compositionmentioning
confidence: 99%